Anarchy and the environment : the international relations of common pool resources - Barkin, J. Samuel, 1965-; Shambaugh, George E., 1963- (State University of New York Press, 1999)
Hypotheses on the International Politics of Common Pool Resources / J. Samuel Barkin and George E. Shambauch -- International Enviromental Common Pool Resources: More Common than Domestic but More Difficult to Manage / Ronald B. Mitchell -- Tune Fishing and Common Pool Resources / Elizabeht R. DeSombre -- Managing Common-Poole Marine Living Resources: Lessons from the Southern Ocean Experience / Christopher C. Joyner -- The Power to Destroy: Understanding Stratospheric Ozone Politics as a Common-Pool Resource Problem / David Leonard Downie -- Asymmetrical Rivalry in Common Pool Resoueces and European Responses to Acid Rain / Barbara Connolly -- Scarcity and Secutiry: A Common-Pool Resouece Perspective / Richard A. Matthew -- Conclusions: Common Pool Resources and International Enviromental Negotiation / J. Samuel Barkin and George E. Shambaugh.